The Impact of Profitability, Dividend Policy, and Capital Structure on the Value of Agricultural Sector Companies on the IDX - Sinaga, Stefie Fiorella; Siallagan, Hamonangan; Munte, Mei Hotma Mariati (Balance Vocation Accounting Journal, 2025)
The agricultural sector in Indonesia faces various economic and policy challenges, so understanding the factors that affect a company's value is urgent in this study. This study aims to analyze the influence of profitability, dividend policy, and capital structure on company value in the agricultural sector listed on the Indonesia Stock Exchange for the 2021–2023 period. The research method uses a quantitative approach with purposive sampling techniques and secondary data analyzed through multiple linear regression with SPSS version 26 software, including classical assumption test and hypothesis test. The results of the study show that profitability and dividend policy have a positive and significant effect on the company's value, while the capital structure has a negative and significant effect. These findings provide practical contributions for managers and investors in financial decision-making, particularly in the agricultural sector. The novelty of this research lies in a comprehensive analysis of the interaction of the three variables (profitability, dividend policy, and capital structure) in the context of Indonesia's agricultural sector, which has not been widely explored in previous research, especially in the post-pandemic period (2021-2023) which is fraught with global economic dynamics and domestic policies.